DISTRIBUTION OF SOME MICRONUTRIENTS IN THE LAKHOTIA LAKE, PALI (RAJASTHAN) - Khatri, T C (Indian Journal of Fisheries, 2011)
The distribution of four nMcronutrients —Fe, Zn, Cu and Mn— are reportedover an annual cycle in the Lakhotia lake, Rajasthan. Total Fe, Zn and Mn werepresent in detectable concentration throughout the year, whereas Cu only duringApril to August. The concentrations of total Fe ranged from 49 to 816 {J-gl-'. Zn,30 to 382 /*gl-', Mn, 74 to 144/^gl-' and Cu, traces to 50 P'g!-'. On a comparisonwith those of temperate lakes the concentrations of all micronutrients in Lakhotialake were higher. An inverse relationship of mioronutrientsi with phytoplanktoewas apparent.